2004
DOI: 10.1111/j.1572-0241.2004.40267.x
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Wall Thickness at Abdominal Ultrasound and the One-Year-Risk of Surgery in Patients with Crohn's Disease

Abstract: Data suggest that bowel wall thickness >7 mm at ultrasound is a risk factor for intestinal resection over a short period of time. Routine use of abdominal ultrasound during evaluation of patients with Crohn's disease may identify a subgroup that is at high risk for surgery. (Am J Gastroenterol 2004;99:1-7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 25 publications
2
32
0
4
Order By: Relevance
“…Moreover, the severity of US findings, particularly a significant increase in transmural thickness, can be a good predictor for the necessity of a surgical intervention [82,86]. US can be considered a surrogate investigation of endoscopy for the assessment of mucosal healing after biological therapy initiation [87].…”
Section: Monitoringmentioning
confidence: 99%
“…Moreover, the severity of US findings, particularly a significant increase in transmural thickness, can be a good predictor for the necessity of a surgical intervention [82,86]. US can be considered a surrogate investigation of endoscopy for the assessment of mucosal healing after biological therapy initiation [87].…”
Section: Monitoringmentioning
confidence: 99%
“…The placement of the nasojejunal tube, necessary for the enteroclysis, is invasive, requires the use of ionizing of patients with CD [39,40] . and in early identifying intraabdominal complications, such as abscesses, fistulae and strictures [41][42][43][44] . The reported sensitivity of US in detecting CD strictures approximately is 74%-80% [41] .…”
Section: Cross Sectional Imagingmentioning
confidence: 99%
“…Several studies showed a relation among bowel wall thickness, clinical disease activity and endoscopic findings, using the Crohn's Disease Activity Index (CDAI) at initial diagnosis and during the clinical course of CD [23,24]. In particular, patients with a wall thickness of more than 7 mm have an increased risk of surgery [25].…”
Section: Ultrasonographic Features Of the Intestinal Wall In Crohn's mentioning
confidence: 99%